Fabrication of alignment polycaprolactone scaffolds by combining use of electrospinning and micromolding for regulating Schwann cells behavior. Issue 12 (7th September 2018) - Zhang, Luzhong; Chen, Shiyu; Liang, Ruyu; Chen, Yi; Li, Shenjie; Li, Siqi; Sun, Zedong; Wang, Yaling; Li, Guicai; Ming, Anjie; Yang, Yumin
Abstract: In the present study, a new approach for fabricating micropatterned polycaprolactone (PCL) scaffolds with ridge/groove structure on the surface was developed by combining use of electrospinning and micromolding method. A series of physicochemical properties, including morphology, wettability, component, crystal pattern and mechanical properties, of prepared PCL scaffolds were characterization, respectively. Stability of the micropatterned PCL scaffolds was measured using phosphate buffer solution immersion for a certain period. Then, the regulating effects of the micropatterned PCL scaffolds on attachment, orientation and normal biological function of Schwann cells were evaluated. And the protein adsorption behavior in various PCL scaffolds was also detected. The results showed that the micropatterned PCL scaffolds demonstrated a porous micro/nano complex structure with enhanced hydrophobicity and mechanical properties as a function of electrospun flow‐rate of PCL solution. The micropatterned PCL scaffolds possessed good stability and could effectively regulate the attachment and orientation of Schwann cells at the early stage after cell culture. Importantly, the electrospun flow‐rate of PCL solution was found to play an important role in scaffold properties, cell behavior and protein adsorption. The micropatterned scaffolds with a flow‐rate of PCL solution at 0.12 mL h −1 demonstrated the better regulation on Schwann cells attachment and alignment without negatively affect the normal biological function of the cells. To the best of our knowledge, this is the first report of combining use of electrospinning and micromolding method for preparing artificial nerve implants. The study is anticipated to have potential application in peripheral nerve and other tissue engineering. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3123–3134, 2018.